2016
DOI: 10.1007/s10603-016-9329-5
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Time Pressure and Stress: Consequences for Families’ Food Consumption

Abstract: This study explores the coping strategies that families apply when under time 3 pressure and stress (time stress) and how such strategies affect food consumption at dinnertime. 4The data was based on photo interviewing methodology with a sample of 12 Norwegian 5 children (ages seven and eight) and their parents. In this case, the children were asked to take 6 photographs during their dinners at home and while shopping for groceries with their parents. 7The findings show that the most dominant explanation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…This study found that when a smartphone application had user-friendly navigation and low time consumption incorporated into the design, the parents were more likely to use it. A previous study found that families' food consumption was hindered based on the parents' time constraints and stress (Alm & Olsen, 2017). If parents have an application that allows them to quickly and efficiently plan their family's meals, the family could have more meals eaten together at home.…”
Section: Increased Family Mealtimesmentioning
confidence: 99%
See 4 more Smart Citations
“…This study found that when a smartphone application had user-friendly navigation and low time consumption incorporated into the design, the parents were more likely to use it. A previous study found that families' food consumption was hindered based on the parents' time constraints and stress (Alm & Olsen, 2017). If parents have an application that allows them to quickly and efficiently plan their family's meals, the family could have more meals eaten together at home.…”
Section: Increased Family Mealtimesmentioning
confidence: 99%
“…This same study also found that if there was not a meal ready to eat, parents opted for unhealthy snacks and convenience foods. Furthermore, when the parents did plan out the family's weekly meals, a higher percentage of healthy meals were consumed (Alm & Olsen, 2017). When parents have a low time consumption method for meal planning for their families, the whole family could have healthier meals.…”
Section: Increased Family Mealtimesmentioning
confidence: 99%
See 3 more Smart Citations